Dual Paraneoplastic Endocrine Syndromes Heralding Onset of Extrapulmonary Small Cell Carcinoma: A Case Report and Narrative Review - Feffer, Jill B.; Branis, Natalia M.; Albu, Jeanine B. (Frontiers in Endocrinology, 2018)
Objective: Extrapulmonary small cell carcinoma (EPSCC) is rare, and frequent metastases at presentation can complicate efforts to identify a site of origin. In particular, SCC comprises <1% of prostate cancers and has been implicated in castration resistance. Methods: Clinical, laboratory, imaging and pathology data are presented. Results: A 56-year-old man with locally advanced prostate adenocarcinoma on androgen deprivation therapy presented with a clogged nephrostomy tube. Laboratory results included calcium 13.8 mg/dL (8.5-10.5 mg/dL), albumin 3.6 g/dL (3.5-5 mg/dL) and potassium 2.8 mmol/L (3.5-5.2 mmol/L). Hypercalcemia investigation revealed intact PTH 19 pg/mL (16-87 pg/mL), 25-OH vitamin D 15.7 ng/mL (>30 ng/mL) and PTH-related peptide (PTHrP) 63.4 pmol/L (<2.3 pmol/L). Workup for hypokalemia yielded aldosterone 5.3 ng/dL (<31 ng/dL), renin 0.6 ng/mL/hr (0.5-4 ng/mL/hr) and 6 am cortisol 82 mcg/dL (6.7-22.6 mcg/dL) with ACTH 147 pg/mL (no ref. range). High-dose dexamethasone suppression testing suggested ACTH-dependent ectopic hypercortisolism. Contrast-enhanced CT findings included masses in the liver and right renal pelvis, a heterogeneous enlarged prostate invading the bladder, bilateral adrenal thickening and lytic lesions in the pelvis and spine. Liver biopsy identified epithelioid malignancy with Ki proliferation index 98% and immunohistochemical staining positive for synaptophysin and neuron specific enolase, compatible with high-grade small cell carcinoma. Staining for ACTH was negative; no stain for CRH was available. Two weeks after chemotherapy, 6am cortisol normalized and CT scans showed universal improvement. Conclusion: Extensive literature details paraneoplastic syndromes associated with SCC, but we report the first case of EPSCC diagnosed due to onset of dual paraneoplastic syndromes.